TFIIIR is an isoleucine tRNA. - Dunstan, H M (1994)
Promoter-specific transcription by silkworm RNA polymerase III is dependent on several transcription factors (TFs) in addition to the polymerase itself. The activities present in silk gland nuclear extracts that are necessary to reconstitute transcription from class III genes in vitro have been resolved into several partially purified components. These include TFIIIR, which is unusual because it is composed of RNA. Here, we identify the RNA that provides TFIIIR activity as silkworm tRNA(IleIAU). This conclusion is based on copurification of tRNA(IleIAU) with TFIIIR activity, TFIIIR activity in synthetic tRNA(Ile), and hybrid selection of TFIIIR activity by antisense tRNA(IleIAU). We have tested the ability of a variety of other tRNAs to stimulate transcription and find that TFIIIR activity is highly specific to silkworm tRNA(IleIAU).